Question jurassienne et idéologies langagières. Langue et construction identitaire dans les revendications autonomistes des minorités francophones (1959-1978) - Cotelli Kureth, Sara (Editions Alphil Presses universitaires suisses, 2015)
This sociolinguistic study analyses the discourse on the language of the Jura autonomist movement. It explores the hypothesis that the language ideologies present in this discourse have participated in the identity construction of the Jura separatists as a francophone linguistic minority endangered under the supervision of the German speaking Berne Canton majority.